Strategic Role of Management Audit in Enhancing Operational Efficiency and Public Value - Angga Christopel Immanuel Lumban Tobing; Annada Nasyaya (Journal of Entrepreneurship and Strategic Management, 2025)
This study aims to analyze the role of management audit as a strategic instrument in enhancing operational efficiency and public value creation in corporatized public sector organizations, using PT Pertamina Hulu Rokan Regional 1 Zone 4A as a case study. Management audit is conceptualized through four dimensions: audit planning, implementation, reporting, and follow up, while operational efficiency is measured across process performance and productivity, resource utilization, and the achievement of outcomes and public value. Data were collected via questionnaires distributed to all employees of the Supply Chain Management unit (N = 78) and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that not all audit stages exert an equal influence on operational efficiency. Audit planning and implementation exhibit relatively weak effects, whereas audit reporting begins to make a significant contribution to outcome achievement and resource utilization. The most prominent finding is audit follow up, which has a positive and significant impact across all dimensions of operational efficiency. This study underscores that management audit should be positioned as an integral component of public sector organizational strategy, with the effective implementation of audit recommendations serving as the key to achieving efficiency and public value. The findings contribute theoretically to public administration scholarship and offer practical implications for strengthening governance in energy sector state-owned enterprises.